Epidemiology and complications of facial fractures: a 5-year retrospective study - María Cristina Zindel-Deboni; Guillermo Lanas; Fernando Paredes; Kleber Vallejo; Andrea Lanas (Universidad de Antioquia, 2019)
Introduction: regional epidemiological studies involving facial trauma are needed to develop more efficient ways of providing health care services. The time elapsed from the occurrence of facial trauma to its definitive treatment can affect clinical outcomes in terms of interventions, resolution, and complications. The aim of this study was to verify if there is a relationship between the different fracture types, their treatments or time intervals for clinical resolution and the onset of complications. Methods: a retrospective study was conducted by means of the clinical records of the Eugenio Espejo Hospital in Quito, verifying the epidemiological data on the clinical evolution of facial trauma patients between 2012 and 2016, and registering data such as age, gender, fracture type, time elapsed until its definitive treatment, and onset of complications. Clinical records lacking these data were excluded. Results: most cases occurred outside Quito (64%). There was no relationship between harmful habits, fracture displacement, type of access or fixation, or presence of comorbidities and the onset of complications. The odds ratio (95% confidence interval) for complications was OR = 0.301(0.170-0.536), so there is a 70% increased chance of developing some complications if treatment is performed one week after trauma occurs. Conclusion: reducing facial fractures before a week can decrease the onset of complications and sequelae.